Circular Business Model Innovation and Its Relationship With Business Performance in Brazilian Industrial Chemical Companies - Francies Diego Motke; Clandia Maffini Gomes; Jordana Marques Kneipp; Ana Paula Perlin; Luana Inês Damke; Tatiane Balbinot Lamberti (Frontiers in Sustainability, 2022)
This study aimed to analyze the relationship between circular business model innovation and business performance in Brazilian industrial chemical companies. This is a quantitative study carried out through a survey with Brazilian industrial companies. Based on a homogeneity analysis (Homals), the results showed that the high degree of innovation in business models from the adoption of circular economy (CE) strategies in the analyzed companies confirms that a significant change leads to superior performance, especially in market, production, economic and financial, and social.